Application of Quantity Theory of Money in Cryptocurrencies: Example of Bitcoin and the Impact of Covid-19 - Seren Fırat; Esat Daşdemir (İstanbul İktisat Dergisi)
This study tests the validity of the quantity theory for cryptocurrencies. They have been on the agenda of financial markets in recent years, and they are perceived as a new type of money. Considering the historical development of money, the emergence of cryptocurrencies is similar to the evolution of traditional currency. Therefore, great deficiency exists in the in the existing literature because money rules are not tested for cryptocurrencies, which have been referred to as the money of the future. Within the scope of this study, releases and the use of cryptocurrencies were comparatively discussed with other types of money, and Fisher’s quantity theory model was tested for crypto coins. Using the market value and amount of Bitcoin, the time series analysis is performed with monthly frequency data covering a period from August 2010 to April 2021. As a result of the analysis, it is understood that a linear relationship prevails between the amount and value of Bitcoin. The main reason for this situation can be explained by cryptocurrency mining activities that use the blockchain method. the econometric analysis shows that the Covid-19 outbreak has strengthened the positive relationship between Bitcoin amount and market value. To understand the results of the analysis and fill the gap in the literature, issues such as money supply, emission and seigniorage income for cryptocurrencies are discussed and the operating processes for each are explained. This study contributes to the literature by showing that the Fisher Quantity Theory is not valid for cryptocurrencies.